Development of a blockchain-integrated medical device for enhanced data integrity - Gunawan, Teddy Surya; Roslan, Nadiah Karmila; Kartiwi, Mira; Md Yusoff, Nelidya (IEEE, 2024)
Integrating blockchain technology with medical devices is crucial for addressing healthcare data integrity and security challenges. Traditional data storage methods are vulnerable to tampering and unauthorized access, compromising patient safety and privacy. This study develops a blockchain-integrated medical device system to create a tamper-resistant framework. The primary objectives are to secure medical device measurements using blockchain, evaluate the system's security against data tampering and unauthorized access, and assess its performance. The methodology includes deploying smart contracts on the Ethereum blockchain to store hashed and encrypted medical data, simulating data generation with a Raspberry Pi, and implementing user authentication through Flask and JSON Web Tokens (JWT). The system achieved an average transaction throughput of 7.72 TPS and a latency of approximately 0.13 seconds, demonstrating robust tamper resistance. These findings indicate that blockchain integration can significantly enhance data integrity and security in healthcare, improving patient outcomes and data privacy within medical ecosystems.